1963
DOI: 10.1002/jcp.1030620313
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of colony‐forming cells among spleen colonies

Abstract: Many of the models of hemopoiesis that have been proposed (see, for example, Cronkite et al., '59) are based on the assumption that the continued production of blood cells requires the presence of progenitor cells with the capacity for continued proliferation. From this point of view, hemopoietic tissue may be considered to consist of two compartments; the first, or stem cell compartment, consists of progenitor cells with the capacity to give rise to progeny consisting of both differentiated cells and new stem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
319
0
7

Year Published

1970
1970
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(330 citation statements)
references
References 6 publications
4
319
0
7
Order By: Relevance
“…The f-value, i.e. the fraction of CFU recoverable from an organ (Siminovitch et al, 1963), was estimated to be about 67 per cent in the above three major organs (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…The f-value, i.e. the fraction of CFU recoverable from an organ (Siminovitch et al, 1963), was estimated to be about 67 per cent in the above three major organs (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Our results confirm and extend the distribution findings obtained by others using both functional assays of retrieved cells and direct analysis of PKH26-labelled cells after injection of either unfractionated or stem cell-enriched populations, all of which have indicated different homing patterns of syngeneic marrow cells to different organs. 7,9,10,[34][35][36] This includes the observation that the proportion of injected marrow cells retained within the spleen and liver declines twoto three-fold during the first day post transplant, in contrast to the marrow and thymus where a stable and in the case of the marrow, an ultimately higher level of engraftment is achieved much faster (70% of maximum within 2 h post transplant). In addition, we show that, as is seen in the spleen and liver, there is a marked decline of the injected marrow cells in the blood during the first day post transplant, although the precise kinetics of the early decline seen in each of these sites appear to be different.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that intravenously injected bone marrow cells disappear rapidly from the circulation of irradiated recipients and very soon after injection begin to accumulate in the marrow and spleen. [7][8][9] The initial lodgment of at least some types of early hematopoietic progenitors in the spleen is, however, transient, as the percentage of injected colony-forming cells (CFC) recovered from the spleen has been found to decrease substantially between 4 and 24 h after their intravenous injection. On the other hand, in the bone marrow, the number of injected CFC increases between 2.5 and 4 h after injection and then remains relatively constant for the next 24 h. 10 Recent evidence indicates that VLA-4, its ligands VCAM-1 and the CS1-motif in fibronectin, as well as the P-and E-selectins are involved both in the homing as well as the mobilization of hematopoietic progenitors.…”
mentioning
confidence: 99%
“…The CFU population in bone marrow of studied genotypes reached 5000-8000 per femur. Taking the seeding efficiency factor as being 0.05-0.1 [10], the CFU population would be 50000 -150000 per femur. Therefore, each pluripotent HSC is capable of producing a clone which includes 500-1500 CFUs and 1-4 x 10 9 differentiating cells (it should be borne in mind that an 8-day spleen colony may consist of 4 x 10 6 cells).…”
Section: Discussionmentioning
confidence: 99%